VECTORS AS MATHEMATICAL OBJECTS - Rozimurodov Rozimrod Narzulloyevich (American Journals Publishing, 2022)
The article examines existing approaches to defining the concept of "geometric vector" in educational literature. A reasonable definition of the concept of "vector quantity" from the point of view of physical and technical sciences is proposed. In real mathematics, the uniqueness of operations on given vectors is studied. Differentiation of vector quantities accepted in mathematical manuals is considered.
Keywords: Vector quantities, set of directed segments, equivalence relation, associated vectors, sliding vectors, axial vectors, polar vectors.